A broadband high-transmission gradient phase discontinuity metasurface. (12th February 2018) - Liu, Yahong; Liu, Congcong; Song, Kun; Li, Meize; Zhao, Xiaopeng
Abstract: Metasurfaces have attracted significant attention due to the control of the electromagnetic waves that they enable. In this paper, we demonstrate a high-transmission gradient phase discontinuity metasurface composed of metallic rods and cylindrical dielectric resonators operating at a broadband microwave frequency from 8 GHz to 9.8 GHz, with a fractional bandwidth of 20.2%. The proposed gradient phase discontinuity metasurface can achieve complete 2 π transmission phase coverage with π /4 phase intervals by varying the geometric parameters of the dielectric resonators and metallic rods. It is shown that the proposed metasurface can refract a normally incident plane wave to an angle of 30°. The broadband metasurface is flexible, and the refracted angle can be adjusted easily by varying the lattice constant. Besides the broadband anomalous refraction, we also demonstrate the metasurface can produce an interesting vortex and wave-focusing in the wide frequency range from 8 GHz to 9.8 GHz. Finally, we demonstrate that the present metasurface can tailor interference wavefronts to plane wavefronts.